How to Promote Interactions Teacher/Students During Confinement Period? (Journal of Education and Development, 2020)
Since 13 March 2020, the establishments in French-speaking Belgium had to offer their distance lessons to curb the spread of the coronavirus (Covid-19). If the universities have material, technological and human resources to offer distance learning to students since several years, the confinement measures have however led the teachers to reorganize their courses started face-to-face by using numeric tools. This article pursues several objectives. On the one hand, it describes a teaching experience report based on the use of the podcast during a course in psychological and educational cursus. On the other hand, based on student's responses to a questionnary, it highlights the advantages and limits of using the podcast during the confinement period. Finally, this article aims to help teachers choose the digital device that corresponds to these pedagogical expectations in a distance education context.